The Role of Midwives in Reducing Maternal Mortality Through Community-Based Health Programs - Mika Sugarni; Raudhatul Munawarah; Zaida Mauludiyah; Ketut Espana Giri; Hadija (CV. Get Press Indonesia, 2025)
Maternal mortality rate (MMR) is an important indicator in assessing the effectiveness of a country's health system. Despite various efforts, the MMR in Indonesia is still high compared to other countries in Southeast Asia. This study aims to analyze the role of midwives in reducing MMR through community-based health programs. The research method used was a quantitative approach with a pretest-posttest design without a control group. The study sample consisted of 50 pregnant women who were selected by purposive sampling in study area X. The intervention program included maternal health education and counseling by midwives. The results showed a significant increase in pregnant women's understanding of pregnancy health, with an average pretest score of 60.04 and increased to 85.6 at posttest (p (00.00) < 0.05). The educational efforts led by midwives have demonstrated effectiveness in enhancing pregnant women's awareness of danger signs during pregnancy, improving nutritional practices, and promoting preparedness for safe childbirth. These outcomes highlight the educational role of midwives as a crucial factor in maternal health interventions, contributing significantly to the reduction of maternal mortality rates (MMR). Strengthening midwives’ capacity and ensuring supportive health policies are essential steps toward optimizing their role in education and achieving the Sustainable Development Goals (SDGs) related to maternal health.